The Museum battle glory of 139th Roslavlth Red Bannerth The Order of Suvorov infantry division at the Lyceum №3 school city Cheboksary - Ivanova I. P. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article tells about activity museum of 139th infantry division. The battle path of 139 infantry division. Importance and relevance to study history issues today for example activities school museum.
Keywords: историческая память; Великая Отечественная война; historical memory; мужество; героизм; школьный музей; The Great Patriotic War; school museum; стрелковая дивизия; rifle division; courage and heroism